2020
DOI: 10.1002/csr.2009
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Configurations and Corporate Social Responsibility Disclosure: Qualitative Comparative Analysis of Audit Committee and Board characteristics

Abstract: Drawing on the complexity theory and responding to the recent calls to use such creative methods that mix between a quantitative and qualitative approach. Therefore, this study fills the literature gap, adding novelties, showing evidence from the unexplored (or underexplored) European context and, consequently, shedding light to inconclusive results in previous research concerning the effect of audit committee (AC) and board characteristics on corporate social responsibility (CSR) disclosure by applying a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(143 citation statements)
references
References 99 publications
(222 reference statements)
10
108
1
1
Order By: Relevance
“…As shown in Table 10, board independence, gender diversity, and board size are the most used variables with frequency of 101, 95, and 71, respectively. On the other hand, few studies on the field of the board of directors and CSR have studied other board variables for example; audit committee characteristics (Dwekat et al, 2020), board age, board education and experience, board tenure, board interlocking, board compensations, CSR committee characteristics. Thus, it could be useful for future research to focus on these variables.…”
Section: Csr Disclosurementioning
confidence: 99%
“…As shown in Table 10, board independence, gender diversity, and board size are the most used variables with frequency of 101, 95, and 71, respectively. On the other hand, few studies on the field of the board of directors and CSR have studied other board variables for example; audit committee characteristics (Dwekat et al, 2020), board age, board education and experience, board tenure, board interlocking, board compensations, CSR committee characteristics. Thus, it could be useful for future research to focus on these variables.…”
Section: Csr Disclosurementioning
confidence: 99%
“…This article can be considered a direct response to these calls as we study ACs in the European economy. Moreover, this article adds to our understanding of the divergent practices related to ACs across European countries, so this study fills the gap in the literature by providing new information and evidence from the unexplored European context (Dwekat et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…One of the most crucial variables that affect the functioning of AC is the independence of its chair. The decisions of an AC are directly affected by AC chair as the chair is the responsible for the planning of entire agenda, AC meetings, coordinating with the board and other committees, setting the objectives of internal audit, and also outline entire audit activities (Appuhami & Tashakor, 2017;Dwekat et al, 2020). Generally, it is suggested that the chairman/chair-person of an AC should be an independent person that have no chair or key position in corporate board.…”
Section: Independent Ac Chairmentioning
confidence: 99%